Schools as learning organisations: the influence of leadership and culture (a mixed methods study in Indonesia) - Listyasari, Winda Dewi (2024)
School as Learning Organisation (SLO) has been proposed as an alternative strategy for school-wide transformation. However, this concept experiences little progress in research and practice. Its implementation in Asian countries also faces problems related to system leaders and culture. This study aims to examine the SLO concept in Indonesian public high schools. It investigates the extent to which the schools have the learning organisation characteristics, examines the influence of leadership and culture in developing them into learning organisations, and identifies challenges in this development.